Counselors' attitudes toward psychedelics and their use in therapy. (19th March 2022) - Hearn, Benjamin G.; Brubaker, Michael D.; Richardson, George
Abstract: The ''psychedelic renaissance'' is generating new evidence for psychedelics' potential to treat numerous mental and substance use disorders. In particular, the United States Food and Drug Administration is poised to approve psychedelic drugs 3, 4 methylenedioxymethamphetamine (MDMA) and psilocybin for the use in psychedelic‐assisted therapy (PAT). This renaissance has led to substantial public attention toward psychedelics, state and local changes to the legal status of psychedelics, and recent increases in the rate of psychedelic use among United States adults. Despite these advancements, the counseling profession has remained relatively disengaged from the research and general discourse surrounding psychedelics and PAT. In response to this gap, this study presents the results of a survey of counseling professionals' attitudes toward psychedelics and PATs. Results suggest counselors' attitudes toward psychedelic use and PATs are mixed, unless they are medically supervised. Furthermore, most counselors see potential in PAT and the need for additional research.